Averting the legacy of kidney disease - focus on childhood - Ingelfinger, Julie; Kalantar-Zadeh, Kamyar; Schaefer, Franz (American journal of hypertension, 2016)
The 11th World Kidney Day will be celebrated on 10 March 2016, around the globe. This annual event, sponsored jointly by the International Society of Nephrology